2022
DOI: 10.1111/1750-3841.16373
|View full text |Cite
|
Sign up to set email alerts
|

Identifying sensory drivers of liking for plant‐based milk coffees: Implications for product development and application

Abstract: The global plant-based product market is growing rapidly, and plant-based milks show promising potential in the coffee beverage sector. This study aimed to identify sensory drivers of liking of plant-based milk coffees for guiding the development of plant-based products with competitive advantages over dairy milk coffees. Twelve coffee samples were prepared with plant-based (oat, soy, almond, and coconut) and dairy (cow) milk. Quantitative descriptive analysis was used to generate sensory attribute terms for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
(47 reference statements)
2
5
0
Order By: Relevance
“…Sensory analysis has shown that consumers exhibit a preference for coffee infused with coconut milk characterized by a sweet and sour profile. This preference aligns with empirical evidence suggesting that sweetness tends to increase the palatability of coffee beverages containing plant-based milks, whereas sourness generally detracts from it. , Therefore, attention to the formulation of ingredient systems is imperative for optimizing flavor, texture, binding, color, and nutritional content in the development of plant-based alternatives with attributes that resonate with consumer preferences. …”
Section: Challenges and Considerationssupporting
confidence: 65%
See 1 more Smart Citation
“…Sensory analysis has shown that consumers exhibit a preference for coffee infused with coconut milk characterized by a sweet and sour profile. This preference aligns with empirical evidence suggesting that sweetness tends to increase the palatability of coffee beverages containing plant-based milks, whereas sourness generally detracts from it. , Therefore, attention to the formulation of ingredient systems is imperative for optimizing flavor, texture, binding, color, and nutritional content in the development of plant-based alternatives with attributes that resonate with consumer preferences. …”
Section: Challenges and Considerationssupporting
confidence: 65%
“…This preference aligns with empirical evidence suggesting that sweetness tends to increase the palatability of coffee beverages containing plant-based milks, whereas sourness generally detracts from it. 249,250 Therefore, attention to the formulation of ingredient systems is imperative for optimizing flavor, texture, binding, color, and nutritional content in the development of plant-based alternatives with attributes that resonate with consumer preferences. 251−253 Consumer motivations for choosing coconut-based alternatives are diverse.…”
Section: Allergies and Potential Adverse Effects Of Coconutmentioning
confidence: 99%
“…a . STREAMS Studies References PRINCIPAL Vgt-Vgn 92 Allen et al [ 42 .I]; Arenas-Gaitán et al [ 8 ], Aschemann-Witzel & Peschel [ 43 ]; Bagci & Olgun [ 18 ]; Boaitey & Minegishi [ 44 ]; Bobić et al [ 45 ]; Brandner et al [ 46 ]; Braunsberger et al [ 47 ]; Brouwer et al [ 48 ]; Bryant [ 49 ]; Cardello et al, [ 50 ]; Chung et al [ 51 ]; Clark & Bogdan [ 20 ]; Cliceri et al [ 3 , 52 ]; Cramer et al [ 53 ]; Crnic [ 54 ]; Estell et al [ 55 ]; Falkeisen et al [ 56 ]; Feltz et al [ 57 ]; Ghaffari et al [ 58 ]; Gili et al [ 59 ]; Graça et al [ 60 .II, 61 ]; Haas et al [ 62 ]; Hibbeln et al [ 63 ]; Hoffman et al [ 64 ]; Isham et al [ 65 ]; Judge & Wilson [ 66 , 67 ]; Kessler et al [ 68 , 69 ]; Krizanova et al [ 70 ]; Krizanova & Guardiola [ 71 ]; Larsson et al [ 72 ]; Ma & Chang [ 73 ]; MacInnis & Hodson [ 74 , 75 ]; Montesdeoca et al [ 76 ]; Moore et al [ 77 ]; Moss et al [ 78 ]; Müssig et al [ 79 ]; ...…”
Section: Resultsmentioning
confidence: 99%
“…The rise in PBM popularity reportedly corresponds with a decrease in dairy milk sales [ 19 ]. Key drivers of this growth of PBM include the upgrading of taste, nutrient fortification, and increasing environmental and health awareness among consumers [ 20 , 21 , 22 ]. Public values related to environmental impact and animal welfare are notable influencers of demand for PBM [ 23 , 24 ].…”
Section: Literature Reviewmentioning
confidence: 99%